Melatonin as an adjuvant therapy in preterm infants with neonatal sepsis, randomized trial - Zeinab A. El-Kabbany; Ola G. El-Farghali; Soha M. Khafagy; Hebatallah A. Shaaban; Heba H. A. Osman; Mohamed H. Metwally (SpringerOpen, 2020)
Abstract Background Neonatal sepsis (NS) is a systemic uncontrolled inflammatory response to an infectious agent, resulting in oxidative stress. Melatonin antioxidant and free radical scavenger proved to be safe in neonates. We aimed to evaluate the efficacy and safety of melatonin as adjuvant therapy in NS. This was an interventional trial conducted on 40 preterm neonates with NS diagnosed on the basis of clinical and laboratory criteria. They were simply randomized to melatonin treated (MT) (n = 20) and conventionally treated (CT) (n = 20) groups. Melatonin was administered at a total dose of 20 mg enterally in two divided doses of 10 mg each, 1 h apart. Malondialdehyde (MDA) was assessed in patients at enrollment, 4 and 72 h later in MT, and 72hours later in CT. Fifteen healthy matched neonates were included as a control. Results There were no significant differences between MT and CT groups regarding baseline sepsis workup. However, total leucocytic count, absolute neutrophil count, and C-reactive protein were significantly higher and platelets were significantly lower in CT compared to MT after 72 h. MDA was doubled in CT while reduced in MT 72 h after intervention (p = 0.000). Mortality was significantly lower in MT. No side effects following melatonin administration were reported. Conclusion Melatonin is effective and safe adjuvant for treatment of NS that improves clinical and laboratory outcomes. Trial registration clinicalTrials.gov Identifier: NCT03295162. Registered 27 September 2017-Retrospectively registered.